2013
DOI: 10.3109/09537104.2013.764493
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mean platelet volume in children with acute rotavirus gastroenteritis

Abstract: We found that MPV could be used as an acute phase reactant in children with rotavirus gastroenteritis. We believe that the current study will contribute to our understanding of MPV as an inflammatory marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
5
35
0
1
Order By: Relevance
“…Rotavirus gastroenteritis is an inflammatory condition and should be evaluated as other inflammatory illnesses. In this context, it is reported that, when there is an active inflammatory disease such as ulcerative colitis, platelet counts rise due to increased inflammatory cytokine activity and breakdown of these increased larger young platelets in inflammation area lowers MPV [1]. As the authors indicated, the decreased MPV in patients with rotavirus gastroenteritis in this study might be associated with high levels of active inflammation.…”
Section: To the Editormentioning
confidence: 50%
See 1 more Smart Citation
“…Rotavirus gastroenteritis is an inflammatory condition and should be evaluated as other inflammatory illnesses. In this context, it is reported that, when there is an active inflammatory disease such as ulcerative colitis, platelet counts rise due to increased inflammatory cytokine activity and breakdown of these increased larger young platelets in inflammation area lowers MPV [1]. As the authors indicated, the decreased MPV in patients with rotavirus gastroenteritis in this study might be associated with high levels of active inflammation.…”
Section: To the Editormentioning
confidence: 50%
“…We read with great interest the article 'Decreased mean platelet volume in children with acute rotavirus gastroenteritis' by Mete et al [1]. The authors concluded that decreased MPV level is associated with rotavirus gastroenteritis and could be used as a negative acute phase reactant in children with this disease.…”
Section: To the Editormentioning
confidence: 99%
“…In addition, NLR and PLR rates were significantly higher. [8,9,10,12,16]. According to the studies, MPV is inversely proportional to platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…Higher MPV levels were independently associated with high hospital mortality after admission to intensive care units [8]. There are many studies in which MPV values are investigated in viral infections [9,10,11,12,13,14,15,16]. In a previous study, some patients with respiratory syncytial virus (RSV) infections had relatively low MPVs.…”
Section: Introductionmentioning
confidence: 99%
“…e found two studies on MP levels in rotavirus gastroenteritis, two on MP levels in patients infected with Entamoeba histolytica and one study on MP levels in children with infectious and non-infectious diarrhea 13-17 . Mete et al and elik et al reported decreased MP values in patients with rotavirus gastroenteritis and suggested using MPV as a negative acute phase reactant [13,14]. [20].…”
Section: Discussionmentioning
confidence: 99%